(untitled) (Holistic Journal of Management Research, 2021)
Indication of a decrease in employee performance as evidenced by the inaccuracy of the time for completion of work by the employee. There are still some employees who find it difficult to overcome all wishes and guests and to be able to complete work on time. In the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia Number PM.53 / HM.001 / MPEK / 2013 concerning Hotel Business Standards Chapter II Hotel Business Article 4 Paragraph (4) describes Non-Star Hotels as referred to in paragraph (2) letter b, does not has a classification of hotel class and can be called a jasmine hotel. The purpose of this research is to determine how much influence motivation and job satisfaction have on employee performance at hotels in Sumedang Regency. The research method in this research uses quantitative methods or better known as survey research. The results showed that to improve employee performance required compensation, career development through education and training, environmental management and additional work support facilities and infrastructure for employees. The author’s suggestion is that there is a need for pension guarantees for employees of jasmine hotel in Sumedang Regency, improving hotel facilities and maintaining consistency of the leadership in conducting supervision, providing additional income for employees who carry out additional tasks outside of working hours.